Efeitos da estimulação coligérnica central sobre a temperatura talâmica durante o exercício físico - William Coutinho Damasceno (2013)
The present study was aimed at investigating physical exercise-induced alterations in the thalamic temperature and whether the central cholinergic stimulation differently modifies the thalamic and abdominal temperatures. Wistar rats (250-350 g) were used in the experiments. In the experiment 1, a guide cannula was implanted in the thalamus to measure the temperature in two treadmill running speeds (21 and 24 m/min, corresponding to 70 e 80% VO2max., respectively) until voluntary effort interruption (VEI). In the experiment 2, two guides cannulae were implanted into the lateral ventricle and thalamus. Immediately after, a temperature sensor was implanted in the abdominal cavity to measure the core temperature during treadmill running at 21 m/min until VEI. In both experiments, before the start of exercise, a temperature sensor was positioned in the thalamus. In the first experiment, the exercise induced an increase in the thalamus temperature in the two running speeds evaluated (37.97 ± 0.05ºC, min 4 vs 37.46 ± 0.04ºC, min 0, 21 m/min; 38.04 ± 0.04ºC, min 4 vs 37.55 ± 0.04ºC, min 0, 24 m/min; p < 0.05). In the second experiment, the rats were subjected to 2 L of physostigmine (10-2 M) or vehicle (alcohol 10%; VEH) injection into the cerebral ventricle. The physostigmine injection attenuated the exercise-induced increase in the thalamic (37.78 ± 0.14ºC PHY vs 39.02 ± 0.10ºC VEH, min 15, p < 0.05) and abdominal (37.50 ± 0.12ºC PHY vs 38.69 ± 0.11C VEH, min 20; p < 0.05) temperatures by approximately 43%. We conclude that the thalamic temperature increase induced by exercise was not different between the intensities tested and that cutaneous heat dissipation induced by central cholinergic stimulation during exercise attenuates proportionally the increase in the thalamic and abdominal temperatures.